Salivary kallikrein-8 as a favorable biomarker for stress response - Şemsi, Rabia; Ergünol, Erdal; Sepici Dinçel , Aylin (Vojnosanitetski pregled, 2024)
Background/Aim. Kallikreins (KLKs) are a group of serine protease enzymes capable of cleaving protein peptide bonds. Besides, they are proteolytic enzymes that mediate the conversion of kininogen (alpha 2-globulin) to bradykinin or kallidin. The aim of the study was to examine whether KLK8 might serve as a novel stress biomarker. Methods. Twenty-four students (17 female and 7 male) were included in the study. The general and dental health of the students were evaluated in the appropriate anamnesis format. Unstimulated samples were collected by Sarstedt® saliva collection tubes as recommended: 08.00–09.00 am, 12.00, and 2.00–3.00 pm on the exam day. KLK levels were measured by a KLK8 Human ELISA kit. Results. The salivary KLK8 levels in the morning (1.25 ± 0.26 pg/mL) were statistically significantly lower than the KLK8 levels pre-exam [at 12.00 (2.89 ± 0.85 pg/mL)] (p = 0.0006). There was also a significant difference in salivary KLK8 levels between pre- and post-exam (1.69 ± 0.39) time points (p = 0.0005). Conclusion. These results show that the differences in salivary KLK8 levels might be related to the degree of stress, indicating that KLK8 may serve as a novel stress biomarker.
Keywords: biomarkers; kallikreins; oral health; saliva; stress, psychological; students, dental